Inheritance of DNA methylation differences in the mangrove Rhizophora mangle. Issue 4 (12th August 2021) - Mounger, Jeannie; Boquete, M. Teresa; Schmid, Marc W.; Granado, Renan; Robertson, Marta H.; Voors, Sandy A.; Langanke, Kristen L.; Alvarez, Mariano; Wagemaker, Cornelis A. M.; Schrey, Aaron W.; Fox, Gordon A.; Lewis, David B.; et al.
Abstract: The capacity to respond to environmental challenges ultimately relies on phenotypic variation which manifests from complex interactions of genetic and nongenetic mechanisms through development. While we know something about genetic variation and structure of many species of conservation importance, we know very little about the nongenetic contributions to variation. Rhizophora mangle is a foundation species that occurs in coastal estuarine habitats throughout the neotropics where it provides critical ecosystem functions and is potentially threatened by anthropogenic environmental changes. Several studies have documented landscape‐level patterns of genetic variation in this species, but we know virtually nothing about the inheritance of nongenetic variation. To assess one type of nongenetic variation, we examined the patterns of DNA sequence and DNA methylation in maternal plants and offspring from natural populations of R. mangle from the Gulf Coast of Florida. We used a reduced representation bisulfite sequencing approach (epi‐genotyping by sequencing; epiGBS) to address the following questions: (a) What are the levels of genetic and epigenetic diversity in natural populations of R. mangle ? (b) How are genetic and epigenetic variation structured within and among populations? (c) How faithfully is epigenetic variation inherited? We found low genetic diversity but high epigenetic diversity from natural populations of maternal plants in the field. In addition, a large portion (up to 25%) of epigenetic differences among offspring grown in common garden was explained by maternal family. Therefore, epigenetic variation could be an important source of response to challenging environments in the genetically depauperate populations of this foundation species. Abstract : Understanding the extent and structure of genetic and nongenetic variation, and their inheritance patterns is key for conservation biology, a field that relies on identifying the capacity of organisms to respond to environmental challenges to better manage conservation efforts. Here, we document the levels and structure of these two sources of biodiversity in the coastal foundation plant Rhizophora mangle and conclude that epigenetic variation (namely DNA methylation) is inherited and could be an important component of diversity for this species. Highlights: We found low genetic but high epigenetic diversity, and that a large portion of epigenetic differences among offspring was explained by maternal family. Epigenetic variation could be an important source of diversity in these populations.